UN NOU CONCURS – O NOUĂ PROVOCARE - SCOBIOALĂ, manager, Departamentul dezvoltare şi comunicare, Genoveva (BIBLIOPOLIS, 2020)
Is noteworthy the recently launched by the Municipal Library experiences the methods of training or non-formal learning. It was tested about initially at one branch of the Municipal Library but with participation of users from other branches. The positive aspects of this practice were highlighted in the contest "The most efficient Reading Time". The purpose of the contest was to optimize organizational modes of reading, identifying innovative ways of reading and perception of the literary text, supporting the education of children and youth. The competition held in March-April and was attended by 23 branches. The participants had to meet certain preconditions, including involvement of the personalities in their activities. The most beautiful results were obtained the libraries that have choose exciting topics, demonstrating inventiveness, creativity, knowledge, fruitful collaboration with invited writers and artists.